PELAKSANAAN PELAYANAN PERPANJANGAN SURAT TANDA NOMOR KENDARAAN (STNK) BERMOTOR (Studi Pada Kantor Samsat Badan Pendapatan Daerah Provinsi Bengkulu) - Zuliadi Zuliadi (Universitas Muhammadiyah Bengkulu, 2019)
Abstract: Mechanism of service implementation of the vehicle registration number (STNK) extension at the SAMSAT Office of Revenue Service Bureau of Bengkulu Province has not been in line with the expectations of the community. There are several problems in the service including the management takes a long time, complicated procedures, the attitude of collusion and nepotism, and the practice of brokers or extortion (extortion). The formulation of the problem in this study is: 1) how is the mechanism of service implementation of the vehicle registration number (STNK) extension at the SAMSAT Office of Revenue Service Bureau of Bengkulu Province?, and 2) what are the factors that hamper the mechanism of service implementation of the vehicle registration number (STNK) extension at the SAMSAT Office of Revenue Service Bureau of Bengkulu Province?. Therefore, this study aims to determine: 1) the mechanism of service implementation of the vehicle registration number (STNK) extension at the SAMSAT Office of Revenue Service Bureau of Bengkulu Province, and 2) the inhibiting factors in the mechanism of service implementation of the vehicle number registration (STNK) extension at the SAMSAT Office of Revenue Service Bureau of Bengkulu Province. This research uses qualitative research methods with descriptive research type. Data is collected through interview, observation and documentation techniques. The data analysis technique uses four steps namely: data collection, data reduction, data presentation, and conclusion drawing. The results of this study indicate that: 1) the implementation of the service extension of vehicle number (STNK) on aspects of reliability, responsiveness, assurance, and empathy is good except in aspects of tangibles (physical appearance) that have not been good, and 2) inhibiting factors in the implementation services for motorized vehicle registration (STNK) extension letters, inconvenience due to narrow spaces, limited number of taxpayers waiting seats, unexpectedly offline networks and some broken computers.